Robotic Welding Technology - Hong T.S.; Ghobakhloo M.; Khaksar W. (Elsevier Ltd, 2023)
Since the first industrial robots were introduced in the early 1960s, the development of robotized welding has been truly remarkable and is today one of the major application areas for industrial robots. Robot welding is mainly concerned with the use of mechanized programmable tools, known as robots, which completely automate a welding process by both performing the weld and handling the part. Robots are quite versatile and hence have been used for a variety of welding types such as resistance welding and arc welding. This chapter describes the development and progress of robotization in welding over the years and also discusses many advantages and disadvantages of different robotic welding technologies. © 2014 Elsevier Ltd All rights reserved.